Optimalisasi Kelembagaan dan Analisis Jabatan guna Mitigasi Risiko Tumpang Tindih pada Usulan Pembentukan UPTD Pengelolaan Sampah di Kota Denpasar - Belvia Agistri Nizwah; Komang Adi Sastra Wijaya (MASALIQ, 2026)
This study is motivated by the fact that organizational structuring often becomes a contested arena between pressures to expand institutional structures and demands for bureaucratic efficiency. It aims to analyze the institutional restructuring process of the Regional Technical Implementation Unit (Unit Pelaksana Teknis Daerah, UPTD) for Waste Management in Denpasar City through the lens of Richard Scott’s three-pillar institutional theory. Using a descriptive qualitative method with a case study approach, the research examines the validation process conducted by the Institutional and Job Analysis Division of the Organizational Bureau on the proposal submitted by the Dinas Lingkungan Hidup dan Kebersihan (DLHK) of Denpasar City to establish two new UPTDs. The findings show that the initial proposal, which was based on a calculated workload of 837,000 hours per year, contained regulatory inconsistencies because it incorporated upstream functions that fall under village authority as stipulated in Pergub Bali Nomor 47 Tahun 2019. Through analysis of the regulative, cultural-cognitive, and normative pillars, the study concludes that the recommended design of “one additional UPTD with repositioned functions” represents an optimal solution for safeguarding village autonomy while ensuring regional fiscal efficiency. These findings underscore the importance of workload validation as an instrument for mitigating organizational obesity within local government institutions.